The CEACAM1-derived peptide QLSN impairs collagen-induced human platelet activation through glycoprotein VI. Issue 1 (2nd January 2020) - Ye, Yujia; Wan, Wen; Wang, Jing; Hu, Wei; Wang, Huawei; Li, Longjun; Sang, Peng; Gu, Yajuan; Li, Deng; Wang, Zhe; Meng, Zhaohui
ABSTRACT: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) regulates collagen-mediated platelet activation through its cytoplasmic immunoreceptor tyrosine-based inhibition motifs (ITIMs). However, the function of CEACAM1's extracellular cleavage fragments is currently unknown. In the present study, we used mass spectrometry (MS) to identify 9 cleavage fragments shed by matrix metallopeptidase 12 (MMP-12), and then we synthesized peptides with sequences corresponding to the fragments. QLSNGNRTLT (QLSN), a peptide from the A1-domain of CEACAM1, significantly attenuated collagen-induced platelet aggregation. QLSN also attenuated platelet static adhesion to collagen. Additionally, QLSN reduced human platelet secretion and integrin αIIb β3 activation in response to glycoprotein VI (GPVI)–selective agonist, convulxin. Correspondingly, QLSN treatment significantly decreased convulxin-mediated phosphorylation of Src, protein kinase B (Akt), spleen tyrosine kinase (Syk) and phospholipase Cγ2 (PLCγ2) in human platelets. These data indicate that the CEACAM1-derived peptide QLSN inhibits GPVI-mediated human platelet activation. QLSN could potentially be developed as a novel antiplatelet agent. Graphical abstract: : QLSN inhibit collagen-induced human platelet activation through glycoprotein VI.